(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The well-known value-based performance measures are Economic Value Added (EVA) and Market Value Added (MVA). EVA and MVA can help managers and shareholders to measure company’s performance in order to create wealth. The main objective of this study is to examine the relationship between EVA and MVA in creating shareholders ‘value. This study has analyzed the performance of 476 public listed companies in Bursa Malaysia. The companies represent 8 sectors and covers data for 10 years period (2007-2016). The findings seem to show a significant relationship between EVA and MVA for Malaysian firms. However, Malaysian firms indeed need some reliable measures that could evaluate their performance thoughtfully and assist investors to make right investment decisions and capital allocation.